Enhancing Allocentric Spatial Recall in Pre-schoolers through Navigational Training Programme - Boccia, Maddalena; Rosella, Michela; Vecchione, Francesca; Tanzilli, Antonio; Palermo, Liana; D'Amico, Simonetta; Guariglia, Cecilia; Piccardi, Laura (Frontiers in Neuroscience, 2017)
Unlike other abilities, children do not receive systematic spatial orientation training at school, even though navigational training during adulthood improves spatial skills. We investigated whether navigational programme training (NPT) improved spatial orientation skills in pre-schoolers. We administered a 12-week NPT to seventeen 4-5 age-ranged children (training group, TG). TG children as well as seventeen age-matched children (control group, CG) who underwent the standard didactics were tested twice before and after (T1) the NPT using tasks tapping on landmark, route and survey representation. We found that TG participants significantly improved their performances in the most demanding navigational task, which is the task tapping into survey representation. The observed improvement was significantly higher than that observed in the CG, suggesting that NPT fostered the acquisition of survey representation. This step is usually achieved by age seven. This result suggests that NPT improves performance on higher-level navigational tasks in pre-schoolers.